PSYCHOLOGY AND COGNITIVE PROCESSES OF STUDENTS GROWING UP IN THE INFORMATION SOCIETY. WE PUSH FOR INFORMATION CULTURE - Shakhripov Mirjalol Jamoliddin's son (European Science Publishing, 2025)
In this article, you will learn about the century characterized by the stability of globalization and the impact of the informationization of our society on children's cognitive processes and psychology.
Keywords: Cognitive processes, child psychology, attitude to information, family environment, modern technologies, information culture.